Knowledge and Attitudes with HIV/AIDS on Adolescent Behavior in Senior High School - Nyoko, Yuneti Octianus; Hara, Maria Kareri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
In East Sumba 2016 there were 111 HIV / AIDS patients. Of that number, majority is 25-35 years old (51.4%) and the most is in Kambera District (28.8%). These studies are to know the relationships between knowledge and attitudes with HIV/AIDS behavior adolescent in senior high school in Kambera District, East Nusa Tenggara Regency. Crosssectional design. The samples are 132 students of Public Senior High School 1 Kambera, Christian Senior High School Payeti and Public Senior High School Vocational 5 Waingapu. The independent variables are knowledge and attitude and the dependent variable are behavior. Analised data use univariate, bivariate and multivariate. Majority of sample from Public Senior High School Vocational 5 Waingapu (37.9%), technical majors (37.9%), male (55.3%), 17 years old (50.8%), number of sources of information from one source (25.0%). Most of the students had less knowledge (68,9%), less attitude (63,6%) and less behavior (62,1%). Bivariate analysis showed good knowledge related 4 times to good behavior (PR=3,621;95% CI=2,341-5,601; p-value <0,001); good attitude related 3 times to good behavior (PR=3,111;95%CI=1,972-4,907;p-value <0.001). Multivariate analysis showed that knowledge was the most relationships with behavior (PR:8,659;95%CI: 3,315-22,618; p-value<0,001) and then attitude (PR:3.075;95% CI: 1,162 - 8,136;p-value 0,024). Schools, government and health services should improve studentsÃ¢â‚¬â„¢ knowledge and students are more active in finding information about HIV/AIDS.Ã‚Â